Analysis of Costs and Environmental Performance on the Valuation of Mining Companies, with Business Scale as a Moderating Variable - Mhd. Hammam Zulkarnain; Verawati Verawati (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study aims to analyze the impact of environmental costs and environmental performance on firm valuation, with firm size as a moderating variable, among mining companies in Indonesia. Research Method: This study employs a quantitative approach using panel data regression analysis (Fixed Effects Model) and Moderated Regression Analysis (MRA). Secondary data were obtained from financial statements, annual reports, sustainability reports, and PROPER ratings of mining companies listed on the Indonesia Stock Exchange for the period 2021–2024. The sample was selected using purposive sampling based on predetermined criteria. Results and Discussion: The results of the study indicate that environmental costs and firm size have a significant negative effect on firm valuation, while environmental performance has no significant effect. Furthermore, firm size does not moderate the relationship between environmental costs or environmental performance and firm valuation. Implications: These findings highlight the importance of improving the quality of environmental information implementation and disclosure to support decision-making and strengthen sustainability reporting standards. Originality: The novelty of this study lies in its examination of the moderating role of company size in the relationship between environmental costs, PROPER-based environmental performance, and firm valuation among Indonesian mining companies during the 2021–2024 period.